Reducing phosphorus losses from agricultural land to surface water - McDowell, Richard W; Haygarth, Philip M (Current opinion in biotechnology, 2024)
Phosphorus (P) enrichment of water impairs its quality by stimulating algal growth and eutrophication, affecting an estimated 1.7 billion people. Remediation costs are substantial, estimated at $1 billion annually in Europe and $2.4 billion in the USA. Agricultural intensification over the past 50 years has increased P use brought into the system from mined fertiliser sources. This has enriched soil P concentrations and loss to surface waters via pathways such as surface runoff and subsurface flow, which are influenced by precipitation, slope, and farming practices. Effective mitigation of losses involves managing P sources, mobilisation, and transport/delivery mechanisms. The cost-effectiveness of mitigation actions can be improved if they are targeted to critical source areas (CSAs), which are small zones that disproportionately contribute to P loss. While targeting CSAs works well in areas with variable topography, flatter landscapes require managing legacy sources, such as enriched soil P to prevent P losses. •Enrichment of surface waters with phosphorus (P) leads to algal growth and eutrophication.•About 27% of agricultural land exceeds optimal soil P levels, posing a risk of P loss to surface waters.•Agricultural P loss driven by soil, fertilisers, crop residues, and livestock.•Much P loss comes from critical source areas (CSAs) with changing topography.•Targeting mitigation actions to CSAs enhances their cost-effectiveness.